Development of a mobile exergame for increasing physical activity in patients with heart failure. (2nd July 2022) - Klompstra, L; Stromberg, A; Berglund, A; Berglund, E; Fallstrom, J; Oradd, H; Jaarsma, T
Abstract: Funding Acknowledgements: Type of funding sources: Foundation. Main funding source(s): Vetenskapsrådet Background: A 10-minute increase a day in physical activity (PA) in patients with heart failure (HF) can have beneficial effects on symptoms, mortality, and hospitalisation risk. Many patients are physically inactive and find it challenging to leave home to participate in physical activity programs, due to symptoms, lack of easily accessible facilities or fear for being exposed to infection (during the pandemic or during flu season). Developing PA interventions that are tailored to the needs and preferences is challenging, as it needs an interdisciplinary approach and active collaboration with patients. A new approach to increase PA is the use of exergames. An exergame is defined as games that requires participants to be physically active or exercise where player's body motion controls the game. Objective: To develop a mobile exergame (called Heart Farming), test the usability of the exergame, and investigate the feasibility for increasing PA in patients with HF. Methods: The study included three phases: (1) Development of a prototype of the exergame; (2) Usability testing and developing, and (3) Assess feasibility of using the exergame in a PA intervention for patients with HF. Results: A prototype of an exergame was developed which has as main goal to walk 10 minutes more a day. Game elements such as goal setting, providing feedback, and social connectivity are included to motivate patients. The patients can play the exergame according to their needs and wishes, e.g., competition, strategic playing, and social interaction. The exergame was created (Figure), tested and refined through an iterative developmental process and by multidisciplinary team with game designers, HF specialists, user representatives and researchers. During usability testing, eight patients within the heart and lung patient organization were invited to test the exergame. Most patients found the game easy to play and enjoyable and thought the game could be helpful to increase their daily walking. The researchers observed that the patients needed support to be able to play the exergame. Proper familiarization and coaching are needed when introducing the game to patients with HF and this was included as an important part in the exergame intervention. The exergame is further developed iteratively by the multidisciplinary team with increased number of user representatives testing the game and giving feedback. In a feasibility study we will test how feasible the exergame is for a PA intervention in patients with HF. Ten patients will receive the game with structured familiarisation and telephone follow-up including coaching for one month. The results of this feasibility testing will be presented during the conference. Conclusion: The exergame Heart Farming seems to be easy and enjoyable to play but needs proper familiarisation and coaching. The results of the feasibility study will show if this exergame can be used in a PA intervention for patients with HF.